European identity and the learning union - Jo Ritzen; Jasmina Haas; Annemarie Neeleman; Pedro N. Teixeira (Institute of Labor Economics (IZA), 2016)
Europe and the European Union are close in values, in culture and in attitudes. Yet the EU has made little attempt to jointly reinforce the emotional attachment to Europe. Member States stress their differences in national identity through education and language. When the EU made the borderlines between European countries less visible, the language boundary remained, standing in the way of easy communication between citizens of different EU countries. We advance the "Learning Union" as a necessary complement to the EU. The Learning Union has three components: contributing to a sense of European belonging, the "communication EU" as well as the "competency EU". Belonging should be reinforced by aiming the content of education at underlining the common heritage, history and the common future. In communication every EU citizen should learn in school to be competent in one common European language (English is the likely candidate), next to one's own language. Competency is essential for competitiveness. Competency is bred by learning in settings decided by pedagogics, not by (the whims of) well-meaning politicians. The Learning Union is at "arm's length" distance from Governments with autonomy and funding designed to incentivize learning goals as well as equality of opportunity. Universities are a special case with regard to increasing competitiveness, but also for their impact on identity. If anything has contributed to a European identity to this day, it has been the exchange of students in full or part time studies in the EU. This brought about far more than the understanding of subjects and the development of competences: it also has enriched inter-European understanding. As next steps, firstly European student mobility should be increased by more transparency on the value added in learning in Higher Education in different EU countries. Secondly, basic education could increasingly be a source of intra-European social cohesion, equality of opportunity and of economic growth if countries would follow the principles of effective schools, of school autonomy and allocate sufficient funding. This would be convergence in structure, not necessarily in content/curriculum.
Keywords: D7; H7; I2; O4; 330; european identity; european citizenship; student mobility; higher education; citizen education; language